Effect of manufacturing method of Cu-Al electrode on performance during electric discharge machining of siliconised silicon carbide (SiSiC). (2020) - Kulkarni, S.C.; Patil, M.S.; Kulkarni, A.V.; Kulkarni, R.M.; Malagi, R.R.
Abstract: One of the most commonly employed non-traditional technique to machine very hard metals with complicated profiles is electrical discharge machining (EDM), wherein the material is removed by striking an electric spark between electrically conducting workpiece and tool electrode. This work is focused with an objective to analyze the effect of process parameters on work piece erosion rate (WER) keeping in view of productivity. The siliconised silicon carbide (SiSiC) is selected as work piece material with a consideration of variety of applications in different fields like: elements subjected to high-temperature environment such as gas turbines, bearings, manufacturing of molds, aerospace and lining of industrial furnaces. Efficient performance of the EDM process is obtained by the cathodic electrode and the anodic work piece. Response surface methodology (RSM) is applied in this study for analyzing the work piece erosion rate (WER) and electrode erosion rate (EER) along with the other influencing parameters like intensity of electric current, spark on-time and spark off-time, keeping flushing pressure constant at all the levels of the experimentation. Modeling of work piece erosion rate and electrode erosion rate is done using response surface methodology with the matrix obtained through Box Behnken Design (BBD). It is observed that there is increase in WER by 40% when Cu-Al (Stir Casting) tool electrode is used instead of Cu-Al (Powder Metallurgy) tool electrode for recommended settings. Hence it is concluded that for machining of SiSiC work material tool electrode manufactured by stir casting method is preferred over tool electrodes manufactured by powder metallurgy technique to increase the productivity.